Postpartum blues reviewed by the risk factors in Indonesia (Journal of Ideas in Health, 2022)
Background: Postpartum blues are known as postpartum sadness that could initiate a more serious mental disorder. It causes a decrease in the mother's interest in her baby, failure to breastfeed, to acts of hurting the baby and themself. Knowing the determinant factors of postpartum blues as a prevention effort is necessary. Therefore, this review aims to assess the factors contributing to postpartum blues, especially in Indonesian mothers. Methods: A review of all peer-reviewed journal-published studies on postpartum blues and its risk factors among Indonesian mothers from 2012 - 2022. The following databases were searched; Google scholars; SpringerLink; and science direct on September 2022 using the keywords "postpartum blues", "maternal blues", "baby blues", "risk factors”, and “Indonesia”.Results: Fifteen studies were included in this review. Risk factors that contribute to the occurrence of postpartum blues are age, salary, education, employment, breastfeeding process, health education after labor, type of labor, labor induction and labor complications, parity, pregnancy status, mother readiness, labor readiness, marriage satisfaction, husband support, and social support.Conclusion: Women with low socioeconomic Status (SES) and primiparous births have a greater risk of suffering from postpartum blues. Therefore, it is necessary to provide psychological assistance to health workers to the mother after giving birth.